1999
DOI: 10.1073/pnas.96.20.11271
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of structural deformations of immobilized single light-harvesting complexes

Abstract: Single assemblies of the intact light-harvesting complex LH2 from Rhodopseudomonas acidophila were bound to mica surfaces at 300 K and examined by observing their fluorescence after polarized light excitation. The complexes are generally not cylindrically symmetric. They act like elliptic absorbers, indicating that the high symmetry found in crystals of LH2 is not present when the molecules are immobilized on mica. The ellipticity and the principal axes of the ellipses fluctuate on the time scale of seconds, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
158
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(168 citation statements)
references
References 21 publications
9
158
0
1
Order By: Relevance
“…Protein molecules with several chromophores, for example, were shown to behave as a single quantum system (10). The close packing of chromophores in such proteins leads to strong interchromophore interaction that gives rise to cooperative effects such as intermittent fluorescence (11,12) and photon-antibunching (10). Single molecule fluorescence studies of green fluorescent protein revealed similar intermittent fluorescence (9).…”
mentioning
confidence: 85%
“…Protein molecules with several chromophores, for example, were shown to behave as a single quantum system (10). The close packing of chromophores in such proteins leads to strong interchromophore interaction that gives rise to cooperative effects such as intermittent fluorescence (11,12) and photon-antibunching (10). Single molecule fluorescence studies of green fluorescent protein revealed similar intermittent fluorescence (9).…”
mentioning
confidence: 85%
“…Recently, various kinds of multichromophoric assemblies like conjugated polymer molecules [7], light-harvesting pigments [8][9][10][11], donor-acceptor substituted biopolymers [12,13] or dendrimers carrying different numbers of chromophores [14,15] have been studied by single molecule spectroscopy. A strong motivation for these experiments relates to the fact that electronic interactions can then be studied without averaging over the properties of an intrinsically inhomogeneous ensemble.…”
Section: Introductionmentioning
confidence: 99%
“…Transitions between delocalized and localized states as observed for a given dimer are attributed to structural fluctuations of the guest-host system. Coherent energy transport is a controversial issue in molecular aggregates like light-harvesting pigments [1][2][3], J aggregates [4], and conjugated polymers [5,6]. While the coherent excitation transfer interaction tends to delocalize the excitation energy among molecules, static and dynamical disorder tend to localize it.…”
mentioning
confidence: 99%